Labour Efficiency of Dairy Farms with Different Types and Sizes in Hajdú-Bihar County - Vántus, András (Acta Agraria Debreceniensis, 2006)
Questions and uncertainties characterised the accession period of Hungary to the European Union. It is evident that only those producers can compete on the market who produce good quality products. Therefore, only dairy farms with extra high quality raw milk production will be successful. Furthermore, on this basis, rural areas will be able to keep their inhabitants one of the most important problems presently. The author examined the process of milk production and the labour efficiency of 18 dairy farms in Hajdú-Bihar County. Mechanization, the quality of the work force and the system of incentives were assessed. Data of produced milk quality were collected too. Because of farms with different types and sizes the circumstances of milk production differ greatly. As a result of data analysis it was found that the working schedule of small and large farms often differed. The most important working processes (milking, feeding, harvesting) are done by family members. In order to increase the efficiency and improve working atmosphere the improvement of wage and incentive systems would be desirable. Labour efficiency indexes show that the efficiency of tie-stall systems is lower than the efficiency of similar size loose-housing systems. It can also be stated; that labour efficiency of similar size loose housing dairies differs greatly so the importance of work-studies should be increased.